Economic Inequality, Regional Development, and Internal Migration in Indonesia - Irfan Teguh Prima; Khoirunurrofik Khoirunurrofik (Institute for Economic and Social Research, 2019)
This study aims to probe the determinants of inter-provincial migration flows in Indonesia and how economic and development changes affect migration patterns. We employ three census periods, 1990, 2000, and 2010. Our study finds that an increase in relative inequality between origin and destination provinces decreases inter-provincial migration and relatively high distance elasticity in Indonesia leads to high migration cost. People are more inclined to migrate due to push factors as opposed to pull factors from the destination region, thus indicating a strong relationship between the level of regional development and the willingness of people to migrate.